Design, synthesis and biological evaluation of novel indole derivatives as gut-selective NaPi2b inhibitors. (15th July 2022) - Ushiki, Yasunobu; Kawabe, Kenichi; Yamamoto-Okada, Kumiko; Uneuchi, Fumito; Asanuma, Yuta; Yamaguchi, Chitose; Ohta, Hiroshi; Shibata, Tsuyoshi; Abe, Tomohiro; Okumura-Kitajima, Lisa; Kosai, Yuki; Endo, Mayumi; et al.
Graphical abstract: Abstract: Intestinal sodium-dependent phosphate transport protein 2b (SLC34A2, NaPi2b) inhibitors are expected to be potential new candidates for anti-hyperphosphatemia drugs. However, a risk of on-target side effects based on the inhibition of NaPi2b in the lung and testis has been reported. In this article, we report on our identification of novel indole derivatives as gut-selective NaPi2b inhibitors with good activity, low systemic exposure and moderate hydrophobicity. In particular, gut-selective compound 27, with even lower bioavailability and lower systemic exposure as compared to previously reported pyridine derivatives, demonstrated excellent phosphate absorption-inhibitory effect in SD rats. Compound 27 has an ideal profile and appears to offer promise as a candidate drug for the treatment of hyperphosphatemia, with minimal risk of side effects due to systemic exposure.